PENGARUH ISLAMIC MARKETING MIX DAN KEPERCAYAAN TERHADAP KEPUTUSAN MENGINAP WISATAWAN MUSLIM DI HOTEL SYARIAH KOTA PEKANBARU - Riko, Setiawan Pandu; Gatot, Wijayanto; Agnes, Alvionita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This research was conducted to test the influence of the Islamic Marketing Mix and Trust variables on Muslim Tourists' Staying Decisions at Sharia Hotels in Pekanbaru City. The population in this study were visitors who were and had previously stayed at the Syariah Hotel in Pekanbaru City. This research consists of three variables, including Islamic Marketing Mix (X1), Trust (X2) and Decision to Stay (Y). The sample in this study was visitors to Pekanbaru City sharia hotels, totaling 100 respondents. In terms of data analysis, this research uses multiple linear regression analysis using the SPPS (Statistical Package for Social Science) application. Based on the hypothesis test carried out, the research results show that the Islamic Marketing Mix has a positive and significant effect on the decision to stay, Trust has a positive and significant effect on the decision to stay. Keywords: Islamic Marketing Mix, Trust, Decision to Stay